Dataset associated to Bioinspired electro-permeable glycans on carbon: Fouling control for sensing in complex matrices - Iannaci, Alessandro; Behan A., James; Myles, Adam; Whelan, Éadaoin; Scanlan, Eoin; Colavita, Paula (Trinity College Dublin, 2020)
Dataset associated with the article "Bioinspired electro-permeable glycans on carbon: Fouling control for sensing in complex matrices"
PUBLISHED
Keywords: Glycan adlayers; Complex matrices; Nanoscience & Materials